2019
DOI: 10.1080/20445911.2019.1626862
|View full text |Cite
|
Sign up to set email alerts
|

Explanations for cultural differences in thinking: Easterners’ dialectical thinking and Westerners’ linear thinking

Abstract: Since Easterners' naïve dialectical thinking, which is contrasted with Westerners' linear thinking, introduced, many cross-cultural studies on human thinking have been conducted, and explanations for the cultural differences have been proposed. First, after examining the robustness of these cultural differences, two existing explanations are discussed in this paper. The first is based on the distinction between Westerners' analytic cognition and Easterners' holistic cognition. This is related to the distinctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 74 publications
0
33
0
Order By: Relevance
“…This discrepancy may be due to cultural differences in thinking style. Coping research has consistently identified the stress-buffering role of active coping in Western countries (e.g., [ 47 , 48 ]), and the adoption of this direct action-oriented strategy matches the linear thinking style that is prominent among Westerners [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy may be due to cultural differences in thinking style. Coping research has consistently identified the stress-buffering role of active coping in Western countries (e.g., [ 47 , 48 ]), and the adoption of this direct action-oriented strategy matches the linear thinking style that is prominent among Westerners [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…People in high-context cultures such as Chinese, utilized more nonverbal or situational information in communicating with others, whereas people in low-context cultures such as American were more direct and verbal in their methods of communication [49]. As people in low-context cultures sometimes find it difficult to understand the nonverbal or situational information, when people from high-context and low-context cultures are negotiating, it is best to rely on a direct method of communication, the negotiators' common denominator [50,51].…”
Section: Cross-cultural Negotiation: Focus On Cognition and Behaviormentioning
confidence: 99%
“…People's motivation or motivational patterns serve an important purpose in that these are the reasons why people choose to engage in certain behaviors or strategies over others [21,22]. Most researchers studying cross-cultural negotiation have focused on the specific values or communication methods that affect negotiation performance [46,51]; while these variables provide an extensive explanation for the differences in people's negotiation behaviors, why people in certain cultures develop values or communication methods that are different from those of others warrants further exploration.…”
Section: Limitations Of Research On Cross-cultural Negotiationmentioning
confidence: 99%
“…Their complex causal models are responsive to an unexpected outcome. Although the explanation is similar, Yama and Zakaria (2019) proposed that Easterners are more dialectical in dealing with an unexpected outcome than Westerners, hence they are more likely to revise the original models using the information of the outcome dialectically than Westerners. We are not very certain which explanation is more valid.…”
Section: Hindsight Bias and Legal Decision Makingmentioning
confidence: 99%